Effects of Citronella (Cymbopogon nardus) Ethanol Extracts and Distillate Dried Powder Waste on Inhibition of Ascaridia galli Development - Sabuna , Cytske; Wihandoyo,; Harimurti, Sri; Nurcahyo, R. Wisnu (International Journal of Poultry Science, 2018)
Objective: The aim of this study was to quantify the bioactive components and antiparasitic activity of distillate citronella (Cymbopogon nardus or C. nardus) essential oil waste. Methodology: A densitometry method was used to quantitatively analyze the bioactive content of citronella waste. The effects of three concentrations of citronella waste extract and exposure time (30, 60, or 90 min) on adult Ascaridia galli (A. galli) worms in vitro from chicken intestines were evaluated. Results: Distillate waste from citronella (Cymbopogon nardus) (DWC) essential oil contains geraniol compounds. Treatment with DWC extract and powder significantly increased the mortality rate of A. galli compare to physiological solution (NaCl 0.9%). However, treatment with both 1.0% DCW and physiological solution (NaCl 0.9%) significantly increased the mortality rate of A. galli. Treatment effects increased significantly across all time points and there were interactions between material and concentration and; material and time points. Conclusion: The geraniol found in DWC may act as an antiparasitic against A. galli worms.